Infrared Spectroscopy : Anharmonicity of Biomolecules, Crosslinking of Biopolymers, Food Quality and Medical Applications - Theophile, Theophanides; Theophile, Theophanides (IntechOpen, 2015)
This informative and state-of-the-art book on Infrared Spectroscopy is addressed to Researchers in Medicine as well as to Pharmaceutical Industry and Agriculture. It features 7 specialized chapters of MIRS and NIRS covering applications in proteins and biopolymers; food quality research and food safety applications; and medical applications, such as Down syndrome disorders of tooth, probing of brain oxygen, the role of CO2 in blood pressure and diagnosis of metastatic cancer. This book highlights the span of modern Infrared applications.
English
Keywords: Spectrum analysis, spectrochemistry, mass spectrometry; Organic chemistry